Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

0214

  • 3 years ago

do anyone know this? f(x) = −3x − 3 and g(x) = 2x + 1, find f over g(−2).

  • This Question is Closed
  1. hba
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    g(-2)=2(-2)+1=-4+1=-3

  2. 0214
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    thanks

  3. hba
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    We have to find f(x)/g(-2)=-3x-3/-3=-3(x+1)/-3=x+1

  4. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy